2024
DOI: 10.3390/buildings14010216
|View full text |Cite
|
Sign up to set email alerts
|

Architectonic Design Supported by Visual Environmental Simulation—A Comparison of Displays and Formats

Juan Luis Higuera-Trujillo,
Juan López-Tarruella Maldonado,
Nuria Castilla
et al.

Abstract: Visual environmental simulations are fundamental in understanding the relationship between the built environment and psychological perception. The remarkable evolution of virtual immersion displays over recent years has provided a series of advantages to the architectural discipline, one of which is that non-specialists now have the potential to better understand architectural spaces. This work aimed to analyse the adequacy of the main displays and formats currently used in environmental simulations. As the ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…In architectural education, especially for virtual tours, the technical features of PC screens, like high resolutions and refresh rates, are key to presenting detailed architectural content effectively. Unlike VR, PC screens' HD or 4K resolutions enhance the depiction of intricate architectural details, while their refresh rates ensure smooth motion, reducing visual fatigue and keeping users engaged (Higuera-Trujillo et al 2024). Their color accuracy and contrast further bring out the true colors and lighting of ancient structures (Shin 2019).…”
Section: Technical Characteristics Of Pc Screensmentioning
confidence: 99%
See 1 more Smart Citation
“…In architectural education, especially for virtual tours, the technical features of PC screens, like high resolutions and refresh rates, are key to presenting detailed architectural content effectively. Unlike VR, PC screens' HD or 4K resolutions enhance the depiction of intricate architectural details, while their refresh rates ensure smooth motion, reducing visual fatigue and keeping users engaged (Higuera-Trujillo et al 2024). Their color accuracy and contrast further bring out the true colors and lighting of ancient structures (Shin 2019).…”
Section: Technical Characteristics Of Pc Screensmentioning
confidence: 99%
“…Their color accuracy and contrast further bring out the true colors and lighting of ancient structures (Shin 2019). The widespread accessibility and user-friendliness of PC screens also make them a viable option for incorporating serious games into architectural learning, highlighting their role as a valuable educational tool (Higuera-Trujillo et al 2024).…”
Section: Technical Characteristics Of Pc Screensmentioning
confidence: 99%
“…In addition to attribution theory, credibility, and immersion, perception is a key factor in understanding tourists' reactions to virtual environments and cultural heritage representations. Perception includes elements such as usefulness, credibility, realism, precision, and abstraction, which collectively shape how individuals experience and evaluate virtual spaces [84].…”
Section: Perception In Cultural Tourism and Virtual Environmentsmentioning
confidence: 99%
“…Higuera-Trujillo et al [84] investigated the effects of different virtual environment displays and formats on users' perceptions. Their study revealed that factors like realism, comprehension of space, ease of orientation, and usefulness in design decisions were interconnected and influenced by the type of display and format used.…”
Section: Perception In Cultural Tourism and Virtual Environmentsmentioning
confidence: 99%